Music for Alice - Say, Allen (Houghton Mifflin, 2004)
A Japanese American farmer recounts her agricultural successes and setbacks and her enduring love of dance. Based on the true life story of Alice Sumida, who with her husband Mark, established the largest gladiola bulb farm in the country during the last half of the twentieth century.